2019
DOI: 10.1109/access.2019.2891988
|View full text |Cite
|
Sign up to set email alerts
|

A Multivariate Homogeneously Weighted Moving Average Control Chart

Abstract: This paper presents a multivariate homogeneously weighted moving average (MHWMA) control chart for monitoring a process mean vector. The MHWMA control chart statistic gives a specific weight to the current observation, and the remaining weight is evenly distributed among the previous observations. We present the design procedure and compare the average run length (ARL) performance of the proposed chart with multivariate Chi-square, multivariate EWMA, and multivariate cumulative sum control charts. The ARL comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
42
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 40 publications
0
42
0
Order By: Relevance
“…The two well-known measures for evaluating control charts' performance are average run length (ARL) and probability to signal (PTS). ARL is well suited for Phase II control charts, [41][42][43][44][45] while for Phase I charts, one is mostly interested in the probability of detecting inconsistent/contaminated samples (or observations). 29,46 Hence, in this study, PTS is used to compare the performance of the charts in Phase I.…”
Section: Performance Evaluation In Phase Imentioning
confidence: 99%
“…The two well-known measures for evaluating control charts' performance are average run length (ARL) and probability to signal (PTS). ARL is well suited for Phase II control charts, [41][42][43][44][45] while for Phase I charts, one is mostly interested in the probability of detecting inconsistent/contaminated samples (or observations). 29,46 Hence, in this study, PTS is used to compare the performance of the charts in Phase I.…”
Section: Performance Evaluation In Phase Imentioning
confidence: 99%
“…They have shown that these adaptive control charts perform uniformly better than their existing counterparts when detecting a range of mean shift sizes. Some related research works may be seen in Reynolds Jr, 9 Capizzi and Masarotto, 10 Scariano and Calzada, 11 Abbasi and Miller, 12 Abbas et al, 13 Haq, 14 Ajadi and Riaz, 15 Adegoke et al, 16 Adeoti and Malela‐Majika, 17 and in the references cited therein.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, [39] proposed a bivariate HWMA scheme based on linear profiles to monitor the intercept, slope and variance parameters using the Bayesian estimation framework and illustrated its efficiency over a number of competitors in Case U. For the multivariate scenario, [40] and [41] studied the performance of the HWMA scheme in detecting shifts in the process mean vector in Cases K and U, respectively. For nonparametric schemes, [42] studied the performance of the HWMA scheme based on the sign and signed-rank statistics to monitor symmetric and skewed distributions which are applicable in the Case K scenario.…”
Section: Introductionmentioning
confidence: 99%